(untitled) (BERBAKTI : Jurnal Pengabdian Kepada Masyarakat, 2024)
Meta-analysis is a method of collecting or reviewing two or more studies to combine, summarize, and review data from previous studies and other researchers. Meta-analysis can be used as a technique in preparing scientific papers which can make it easier for teachers and pre-service science teacher students to write scientific papers. However, in practice, the ability of teachers and pre-service science teacher students in Ngawi to compose scientific articles is still relatively low. This could be due to the low motivation of teachers and pre-service science teacher students in Ngawi in participating in self-development activities, especially for writing scientific papers. It is hoped that this science meta-analysis scientific writing training activity can grow the insight of teachers and pre-service science teacher students in Ngawi regarding the preparation of science meta-analysis scientific papers, develop the soft skills of teachers and pre-service science teacher students in Ngawi in preparing meta-analysis scientific papers science analysis, producing science meta-analysis scientific papers, and knowing participant satisfaction in participating in science meta-analysis scientific paper training activities. This training activity consists of three stages, namely planning, implementation and evaluation. The method for analyzing data from survey results on training participant satisfaction levels is described quantitatively in the form of numerical percentages. The percentage of numbers shows the participants’ understanding, usefulness, and ability in creating aspects of writing scientific articles. Data is presented in table format, showing relationships between data and simplifying the process of presenting data, analyzing data and drawing conclusions. Overall the training activities went very well and smoothly. Feedback from participants in the "Science Writing Meta-Analysis of Science" training showed a satisfaction score with a very satisfied level and an average percentage of 93.6%.